2010
DOI: 10.4103/0256-4947.71062
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-1 beta (-511C/T) polymorphisms with osteoporosis in postmenopausal women

Abstract: BACKGROUND AND OBJECTIVES:Osteoporosis is a common disease of the elderly, in which genetic and clinical factors contribute to the disease phenotype. Since the production of interleukin-1 (IL-1) has been implicated in the bone mass and skeletal disorders, we investigated whether IL-1 system gene polymorphisms are associated with the pathogenesis of osteoporosis in postmenopausal Taiwanese women.METHODS:Osteoporosis is diagnosed by dual-energy x-ray absorptiometry, which measures bone mineral density (BMD) at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
1
13
0
4
Order By: Relevance
“…According to published data, the National Osteoporosis Foundation (NOF) estimates that as many as 54 million Americans have osteoporosis and decreased bone mass (13). Studies have shown that approximately half of the female and one quarter of the male population will suffer from bone fractures due to osteoporosis (4,5). More than 50% of non-Hispanic Caucasian and Asian women aged 50 years and older have a decreased bone mass, thus increasing their risk for osteoporosis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…According to published data, the National Osteoporosis Foundation (NOF) estimates that as many as 54 million Americans have osteoporosis and decreased bone mass (13). Studies have shown that approximately half of the female and one quarter of the male population will suffer from bone fractures due to osteoporosis (4,5). More than 50% of non-Hispanic Caucasian and Asian women aged 50 years and older have a decreased bone mass, thus increasing their risk for osteoporosis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that IL-1β genic polymorphism plays the role in pathogenesis of osteoporosis in postmenopausal women, which is an independent risk factor for osteoporosis (23). It has also been demonstrated that in postmenopausal osteoporotic women IL-1β, IL-1β/IL-1α ratio and IL-1 bioactivity are elevated, and that they return to premenopausal values only 15 years after menopause (24).…”
Section: Discussionmentioning
confidence: 98%
“…Являясь мощным стимулятором костной резорбции in vitro и in vivo, этот провоспалительный цитокин повышает про-дукцию белка RANKL, увеличивает его активность и сти-мулирует остеокластогенез [30]. В ряде исследований на-блюдалась ассоциация полиморфизма гена IL1β с МПК и предрасположенностью к ОП у женщин в постменопа-узе [20,21]. U. Dundar и соавт.…”
Section: Il10 Mhtfr Pparg Spp1 Ccr5 (59029g/a) и динамикой мпк в unclassified
“…Поэтому мы решили изучить возможное влияние генетических вариантов ряда генов, участвую-щих в детерминации МПК, на антирезорбтивный эф-фект 12-месячного лечения БФ. Помимо уже изученных полиморфизмов генов VDR и IL1β, в настоящем иссле-довании мы оценивали несколько других генов, ассоци-ированных с МПК, включая ген МСР1, кодирующий моноцитарный хемоаттрактантный белок 1 [15], ген LEPR, кодирующий рецептор лептина [16,17], ген IL10 [18], ген MHTFR, кодирующий метиленгидротетрафо-лат редуктазу [19], ген IL1β [20,21], ген SPP1, кодирую-щий белок остеопонтин [22], ген CCR5, кодирующий ре-цептор хемокина CCR5 [16], ген PPARG, кодирующий рецептор -активатор пролиферации пероксисом типа gamma [23].…”
unclassified